(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluating the quality of life of radiation cancer patients at a Hanoi oncology hospital. Methods: Utilizing the standardized EORTC QLQ-C30 questionnaire, we assessed the quality of life for 399 cancer patients undergoing radiotherapy at two timepoints: the commencement of hospitalization and one month post-treatment. Patient quality of life is evaluated through five functional domains, each consisting of yes-no questions, 15 symptom-related questions with four rating levels (1-no symptom, 4-severe symptom), and seven questions concerning the patient’s overall well-being (1-very bad, 7-very good). The study aimed to determine the degree of radiotherapy’s impact on patients’ quality of life. Evaluation was based on the total Raw Score (RS) and converted Score (S). Higher scores indicated a greater impact. Results: Compared to one month after treatment, most functional activities (physical, role, emotional, cognitive) and general quality of life during hospitalization exhibited higher scores. Social function, however, demonstrated a higher score post-treatment (2.59) than at admission (2.39). Fatigue, pain, and insomnia were prevalent issues among patients, with scores of 2.80, 2.66, and 2.88, respectively. The majority of patients (76.7%) reported an impact on their overall quality of life during hospitalization; this rate significantly decreased to 5% of patients one month post-treatment. Fatigue, nausea/vomiting, and pain were the most common symptoms during hospitalization, affecting over 50% of patients in both time periods. Other symptoms, including insomnia, anorexia, and sexual dysfunction, also displayed high incidence rates ranging from 22.5% to 98.3%. Conclusion: These findings suggest that radiotherapy can have a significant impact on patients’ physical and emotional well-being, highlighting the need for multidisciplinary care approaches that address both clinical and psychosocial aspects of treatment.